The Use of Artificial Intelligence in Process Planning - CHU, Chao-Hsien (Institutional Knowledge at Singapore Management University, 1988)
During recent decades, the emergence of artificial intelligence (AI) from computer science, psychology and linguistics has created a great impact on the design and implementation of process planning systems. This article provides a review of the state-of-the-art AI-based automated process planning systems. A generalised framework for expert process planning systems is proposed and prospective research issues are discussed.